PERLINDUNGAN TERHADAP PEREMPUAN DARI TINDAK PIDANA PERKOSAAN BERDASARKAN HUKUM HUMANITER - Arlina Permanasari (Hukum Pidana dan Pembangunan Hukum, 2019)
Abstract Sexual violence including rape during armed conflict is a criminal offense that committed long ago even before World War I and still continues to occur in recent conflicts. The Geneva Conventions of 1949 and their Additional Protocols regulating the protection of victims of conflict in both international and non-international armed conflicts provide special protection to women by respecting the dignity, family dignity and rights of women in armed conflict. The only article that regulates rape, forced prostitution and other sexual violence is only found in Article 27 paragraph (2) of Geneva Convention IV in international armed conflict and Article 4 of Additional Protocol II 1977 (in non-international armed conflict)  which receives a lot of criticism because it does not fully regulate rape substantially, even it is not included as a grave breah of the Geneva Convention. State practice through the international tribunals namely ICTR and ICTY in the Akayesu, Furundžija and Kunarac cases which was finally integrated in the Elements of Crimes of ICC Statute establishes legal protection for women from sexual violence including rape during wartime, which is relatively more normatively acceptable at both the international and national levels.   Keywords: rape, forced prostitution, indecent assault, ICC Statute elements of crimes, humanitarian law.